Práticas interprofissionais colaborativas para um cuidado seguro na estratégia saúde da família - Binotto, Cibele Correia Semeão (Universidade Federal de São Carlos, 2023)
This research aims to analyze the relationships between collaborative interprofessional practice and patient safety in the Family Health Strategy. The method used was exploratory quali-quantitative, of exploratory sequential character, with approval from the Ethics Committee on Research with Human Beings, opinion no. 4,280,360. In the first part of the research, the main characteristics of collaborative interprofessional practice in health, as well as safe care in primary health care, were identified based on scientific evidence through a scoping review. The empirical part of the study took place in the setting of family health units in a city in the interior of the state of São Paulo. Initially, the Team Climate Scale (ECTE), a self-applicable instrument based on the concepts of shared conceptions and organizational climate, constructed in the theory of the four factors of climate for innovation in teamwork, was applied to family health professionals with the aim of identifying units with better team climates. The inclusion criteria for this stage were to belong to the team of these units for more than six months, and for exclusion, professionals on vacation or absent during the data collection period. The data from this stage were analyzed using descriptive statistics. A total of 202 nursing professionals (superior and technical), medicine, dentistry (superior and auxiliary), and community health agents participated in the study. Eight teams presented the most favorable climate, and of these, 3 presented at least one member from each professional category, inclusion criterion for the qualitative stage. In this stage, focus groups were conducted with the 3 selected teams, using a guiding questionnaire that allowed the identification of actions favorable to safe care. The focus groups were recorded and transcribed. The product of the transcription was treated in the IRAMUTEQ software and analyzed in the light of the theoretical framework of collaborative interprofessional practices and safe care. Six classes were formed entitled: implementation of safe care, work objectives, decision making, care construction, team communication, and actions that integrate safe care. The way each member performs their role, the understanding of work objectives, communication in the work process, how care is offered, and how team disagreements are worked out reflect on performance and work resolvability. Thus, factors related to safe care and team climate, such as job satisfaction, are influenced by the way the team interacts in their daily lives.
Collaborative interprofessional practices for safe care in the family health strategy
Keywords: Relações interprofissionais; Equipe de assistência ao paciente; Atenção primária; Interprofessional relations; Patient care team; Primary health care; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA